Mortgage Finance and Culture - Núria Rodríguez-Planas (Institute of Labor Economics (IZA), 2018)
Using a nationally representative sample of 12,344 immigrants from 41 different countries of ancestry living in Spain in 2007, we find that the higher the housing-loan penetration in the country of ancestry, the higher the likelihood of having a mortgage in Spain. Similarly, the higher the mortgage depth in the country of ancestry, the higher the present value of the monthly mortgage payments. Our results suggest that social norms regarding mortgage finance in the country of ancestry matter in determining immigrants' mortgage finance in the host country. More specifically, the effect of social norms on the decision to have a mortgage (the extensive margin) and the amount of the mortgage payments (the intensive margin) is about one third and tenth the size of the effect of having a college degree on mortgage debt, respectively. Evidence of strong persistence of culture among those with longer tenure in the host country, those who immigrated as children or young adults, and second-generation immigrants suggests that vertical transmission of beliefs (from parents to children) is a plausible channel of transmission. Perhaps most importantly, we find that cultural attitudes regarding property rights are most relevant when explaining individuals' decision to get a mortgage, but those regarding credit information matter most when explaining the amount of the mortgage debt.
Keywords: G21; G28; Z13; 330; housing-loan penetration; mortgage depth; culture; formal and informal institutions; and epidemiological approach